Photocatalytic Material–Microbe Hybrids: Applications in Environmental Remediations - Yu, Yadong; Wang, Shanshan; Teng, Jinrui; Zupanic, Anze; Guo, Shuxian; Tang, Xiaobin; Liang, Heng (Frontiers in Bioengineering and Biotechnology, 2022)
Environmental pollution has become one of the most urgent global issues that we have to face now. Searching new technologies to solve environmental issues is of great significance. By intimately coupling photocatalytic materials with microbes, the emerging photocatalytic material–microbe hybrid (PMH) system takes advantages of the high-efficiency, broad-spectrum light capture capability of the photocatalytic material and the selectivity of microbial enzymatic catalysis to efficiently convert solar energy into chemical energy. The PMH system is originally applied for the solar-to-chemical production. Interestingly, recent studies demonstrate that this system also has great potential in treating environmental contaminations. The photogenerated electrons produced by the PMH system can reductively decompose organic pollutants with oxidative nature (e.g., refractory azo dyes) under anaerobic circumstances. Moreover, based on the redox reactions occurring on the surface of photocatalysts and the enzymatic reactions in microbes, the PMH system can convert the valences of multiple heavy metal ions into less toxic or even nontoxic status simultaneously. In this review, we introduce the recent advances of using the PMH system in treating environmental pollutions and compare this system with another similar system, the traditional intimately coupled photocatalysis and biodegradation (ICPB) system. Finally, the current challenges and future directions in this field are discussed as well.